Estabilidade de treliça abatida de material hiperelástico - Santos, Antônio Adryel Lima dos (2021)
The study of the stability of truss slaughtered hyperelastic material is part of the research line of nonlinear dynamic stability of structural elements. In this work, an analytical solution is initially used, where the equations that govern the structural system of a flat truss of two bars, hyperelastic, symmetrical and asymmetric, are obtained from the variation of the system's energy functional, using the Euler-Lagrange equations. The incompressible hyperelastic material is described by the neo-Hookean constitutive model, also considering geometric nonlinearity in the study. The Finite Element Method (FES) is used through the ABAQUS® finite element commercial program to perform static and dynamic analyses to verify the influence of bending efforts on the behavior of the trusses studied. Thus, the main stresses, buckling load and the balance paths of the external forces and axial loads on the bars are obtained in static analysis. From dynamic analysis, frequency-load, frequency displacement, phase planes and responses in time under forced vibration are obtained. The results obtained allow us to conclude that the presence of bending efforts led to higher values for the natural frequency and limit load of the structure.